Analytical fluid dynamics - Emanuel, George (CRC Press, 2016)
"New Edition Now Covers Shock-Wave AnalysisAn in-depth presentation of analytical methods and physical foundations, Analytical Fluid Dynamics, Third Edition breaks down the "how" and "why" of fluid dynamics. While continuing to cover the most fundamental topics in fluid mechanics, this latest work emphasizes advanced analytical approaches to aid in the analytical process and corresponding physical interpretation. It also addresses the need for a more flexible mathematical language (utilizing vector and tensor analysis and transformation theory) to cover the growing complexity of fluid dynamics. Revised and updated, the text centers on shock-wave structure, shock-wave derivatives, and shock-produced vorticity; supersonic diffusers; thrust and lift from an asymmetric nozzle; and outlines operator methods and laminar boundary-layer theory. In addition, the discussion introduces pertinent assumptions, reasons for studying a particular topic, background discussion, illustrative examples, and numerous end-of-chapter problems. Utilizing a wide variety of topics on inviscid and viscous fluid dynamics, the author covers material that includes: Viscous dissipationThe second law of thermodynamicsCalorically imperfect gas flowsAerodynamic sweepShock-wave interferenceUnsteady one-dimensional flowInternal ballisticsForce and momentum balanceThe Substitution PrincipleRarefaction shock wavesA comprehensive treatment of flow property derivatives just downstream of an unsteady three-dimensional shockShock-generated vorticityTriple pointsAn extended version of the Navier?Stokes equationsShock-free supersonic diffusersLift and thrust from an asymmetric nozzleAnalytical Fluid Dynamics, Third Edition outlines the basics of analytical fluid mechanics while emphasizing analytical approaches to fluid dynamics. Covering the material in-depth, this book provides an authoritative interpretation of formulations and procedures in analytical fluid dynamics, and offers analytical solutions to fluid dynamic problems."--Provided by publisher